2013
DOI: 10.3389/fpsyg.2012.00605
|View full text |Cite
|
Sign up to set email alerts
|

Growing Up with Asperger’s Syndrome: Developmental Trajectory of Autobiographical Memory

Abstract: Autobiographical memory (AM) and social cognition share common properties and both are affected in autism spectrum disorders (ASD). So far, most of the scant research in ASD has concerned adults, systematically reporting impairment of the episodic component. The only study to be conducted with children concluded that they have poorer personal semantic knowledge than typical developing children. The present study explores the development of both components of AM in an 8-year-old boy diagnosed with Asperger’s sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Only a very few studies have explored the detail retrieved in ASD (see Bon et al, 2012). The studies report conflicting findings.…”
Section: Neurodevelopmental Disordersmentioning
confidence: 99%
“…Only a very few studies have explored the detail retrieved in ASD (see Bon et al, 2012). The studies report conflicting findings.…”
Section: Neurodevelopmental Disordersmentioning
confidence: 99%
“…In children with ASD, both semantic and episodic AM is reduced (Bruck et al, 2007 ; Bon et al, 2012 ; Goddard et al, 2014 ), though by adulthood, adults with ASD show a spared memory for semantic AM, alongside reduced episodic AM (Klein et al, 1999 ; Crane and Goddard, 2008 ). These studies suggest that as semantic AM may grow in ASD, episodic AM impairments are pervasive.…”
Section: Introductionmentioning
confidence: 99%
“…Examining episodic AM for different periods in participants' lifetimes, studies have found that AM in ASD follows typical patterns of memory deterioration—with more specific memories for recent than remote events—in both adults (Crane and Goddard, 2008 ; Tanweer et al, 2010 ) and children (Bruck et al, 2007 ; Goddard et al, 2014 ; but see Bon et al, 2012 ). Interestingly, Crane and Goddard ( 2008 ) found that adults with ASD lack the typical increase of memories around adolescence years (the “reminiscence bump”) that is associated with identity-building memories.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been observed in neuropsychiatric disorders that are known to impair social cognition. In a longitudinal case study charting the development of a child with autism spectrum disorder, Bon et al (2012) Spreng Examining the role of memory in cognition present an evolving picture of atypical autobiographical memory functioning. In their review, Dimaggio et al (2012) report that shared impairments in autobiographical memory and mentalizing are present in both psychiatric and personality disorders and these deficits need to be considered in treatment and intervention protocols.…”
mentioning
confidence: 99%